Real-time image dynamic range compensation for an optical imaging system - Sim, K. S.; Tso, C. P.; Tan, Y. Y.; Law, K. K.; Teoh, A. B. J. (I S & T - SOC IMAGING SCIENCE TECHNOLOGY, 2007)
This paper presents the development and implementation of a real-time dynamic range compensation system for optical images. Compared with conventional automatic brightness contrast compensators that are based on the average image or pixel intensity level, the proposed system utilizes histogram-profiling techniques to continuously compensate for the dynamic range of the processed video signal. The algorithms are implemented in real time with a frame grabber card forming the front-end video capture element. The proposed technique yields better image compensation compared with conventional methods. Various methods are used in order for the analysis to be statistically valid. (c) 2007 SPIE and IS&T.